Potret Perempuan dalam novel Lebih Senyap Dari Bisikan karya Andina Dwifatma - Rifqi, Nadhil Muhammad; Pangesti, Nesa Riska (Universitas Negeri Padang, 2024)
This study aims to describe the portrait of women in the novel Lebih Senyap dari Bisikan by Andina Dwifatma. This research focuses on three aspects: (1) portrait of single women, (2) portrait of women as wives, and (3) portrait of women as mothers. This research uses descriptive qualitative method with the novel Lebih Senyap dari Bisikan by Andina Dwifatma as the research object. The research data are words, phrases, clauses, and sentences that describe women's portraits. The data collection technique is done by reading and understanding the novel, marking relevant data, and inventorying the data. Data analysis was conducted by data classification, data interpretation, and conclusion drawing. The results showed that the novel More Silent than a Whisper by Andina Dwifatma presents a complex and multidimensional portrait of women. The portrait of a single woman is described as independent, ambitious, and has doubts about marriage. The portrait of a woman as a wife is described as loving, strong, and able to adapt to difficult situations. The portrait of women as mothers is described as loving, protective, and willing to sacrifice for their children. This research is expected to contribute to the understanding of the representation of women in Indonesian literature.